Analysis of the Effectiveness of Using VHF Radio Channel 12 to Assist the Maneuvering Guidance Process on the Km. Binaiya Ship - Risma Yanuar Azizah; Firdaus Sitepu; Dian Junita Arisusanty; I'ie Suwondo (International Journal of Science and Environment (IJSE), 2026)
Indonesia's vast maritime domain demands effective VHF radio communication for safe ship maneuvering amid congested routes, as mandated by SOLAS Chapter IV GMDSS for vessels over 300 GT; Channel 12 supports pilotage coordination on KM. Binaiya, yet technical faults, SOP non-compliance, and traffic density hinder efficacy. This qualitative descriptive study aims to analyze influencing factors and impacts, using Purposive Sampling of 5-10 crew (captain, officers, radio operators), semi-structured interviews, observation sheets, SMCP SOP documentation, and Miles-Huberman analysis (reduction, display, verification). Findings reveal technical issues (noise, corrosion, irregular self-tests), inconsistent SMCP SOP (read-back lapses), and high traffic (eg, 7,000–12,000 ships/week in Makassar) cause overlaps; impacts include reduced clarity, coordination delays, increased collision risks. VHF Channel 12 efficacy is suboptimal; recommend routine training, maintenance, VTS oversight. Future research: quantitative SNR analysis